The Intersections of Student Engagement and Academic Integrity in the Emergency Remote ‘English for Academic Purposes’ Assemblage - Vasilopoulos, Eugenia (Gene); Bangou, Francis (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2022)
This paper explores the disruption of space, place, and material conditions brought on by the migration of traditional on-site language teaching to emergency remote teaching (ERT) in an English for Academic Purposes (EAP) program designed to bridge international students into higher education. We focus on two aspects of language teaching considered essential to academic success: student engagement and academic integrity. Through the Deleuzian concept of assemblage and post-qualitative inquiry, data vignettes from interviews with 12 teacher participants are presented to examine the contingency and relationality between the affordances of technological tools and the absence of embodied connection brought on by the move to ERT. Data vignettes are linked to map how instructors’ perceptions of student engagement mediated through space, place, and materials, inadvertently shape/are shaped by perceptions of academic dishonesty.